(3OQQ GdfMhQs - (3GdSfHSj GdWGFj GdMdj, Uaj GdOjf, YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe, (B750 (3g`s
(3ChdgG (B:s
(3MQa GdCda(B: (3CHJ GdhUGd eNGaI GdQbHGA (B*** (3hCJjc JMJ eOGQY GdXdeGAs
(3BNQgG (B:s
(3jGaY GdYhO UGMH GdLhO (B*** (3MJa GdYO haJM Gdhdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 18s
(3eYLe GdeDdajf(B: 2 / 160s
(3cTa GdXfhf(B: 1 / 750s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs